Nasal and hand carriage of bacteria in different groups of persons in a teaching hospital in India - Ganguly, Parthasarathi; Yunus, Mohammad; Khan, Asif-Uz- Zaman; Malik, Abida (Indian Journal of Community Health, 1995)
275 persons of different categories were studiedfor nasal and hand carnage of different pathogenic bacteria. Overall carriage rate was 54.5%. Doctors and paramedical staff had higher bacterial carriage rate in comparison to other groups. Though Staphylococcus aureus iwu the commonest organism isolated from both nose and skin, earners of Escherichia coli. Pseudomonas and Klebsiella group ofgramnegative bacilli was also observed. Nasal carrier were commonest than dermal carriage